The school health program: teachers' perceptions - Cícero Tavares Leite; Maria de Fátima Antero Sousa Machado; Roberta Peixoto Vieira; Mirna Neyara Alexandre de Sá Barreto Marinho; Claudete Ferreira de Souza Monteiro (Universidad de Antioquia, 2015)
Objective. Understand teachers' perception of a school health program and its relationship with health education activities developed at school. Methodology. Descriptive qualitative study, in which interviews with 10 teachers at a public school in the city of Barbalha, Ceará, Brazil were conducted. Data were analyzed in thematic categories. Results. Teachers perceived the School Health Program as welfare, without integration between teachers and health professionals, and being of no interest to teenagers. Educational activities at school and their relationship to the program were perceived as clinical evaluations that were not integrated into the actions already developed at school. Conclusion. A weakness was found in the lack of integration of actions performed by different agents. Therefore, there is a need for a closer relationship between them in order to optimize efforts to promote school health.